The course of radiographic loosening, pain and functional outcome around the first revision of a total hip arthroplasty - Aghayev, E.; Teuscher, R.; Neukamp, M.; Lee, E.; Melloh, Markus; Eggli, S.; Röder, C. (2013)
Background: The published data on pain and physical function before and after revision of total hip arthroplasty (THA) is scarce. The study reports the course and interrelationships of radiographic loosening, pain and physical function 5 year before and after a first revision THA. Methods. The study was based on the IDES-THA database. All patients with their first THA revision for aseptic loosening and a documented index surgery on the same side and at least one pre-revision and one post-revision follow-up were selected. Only patients with an intact contralateral hip joint (Charnley class-A) were included. Follow-ups within ±5.5 years around the revision time point were analyzed. Annual prevalences of radiographic component loosening and the non-desired outcomes (moderate/severe/intolerable pain, walking <30 minutes, hip flexion range <90°) were calculated. Results: Signs of radiographic component loosening started to increase about 4 years before revision surgery. Two years later, a sharp increase of painful hips from 15% to 80% in the revision year was observed. In the year after revision surgery, this rate dropped back to below 10%. Walking capacity started to noticeably deteriorate 3 years before revision and in the revision year about 65% of patients could not walk longer than 30 minutes. As opposed to pain, walking capacity did not recover to pre-revision levels and the best outcome was only reached two years post-revision. Hip flexion range had the slowest and least extent of deterioration (˜45% flexed <70° in the revision year) but with the best outcomes at only three years after revision surgery it took the longest to recover. Conclusion: Prevalence of radiological loosening signs and/or pain intensity follow an almost parallel course around the first revision of a THA for aseptic component loosening. This process begins about 4 years (radiographic loosening) before the actual revision surgery and intensifies about 2 years later (pain). It also involves walking capacity and hip range of motion. While pain levels go back to levels similar to those after primary surgery, range of motion and even more walking capacity remain moderately compromised. © 2013 Aghayev et al.; licensee BioMed Central Ltd.